An assessment of Pakistani pharmacy and medical students’ knowledge of black box warnings - Murtaza, G.; Khan, S. A.; Murtaza (Junior), G.; Javed, K.; Akram, F.; Hamid, A. A.; Hussain, I. (Acta Bioethica, 2014)
Food and Drug Administration delivers the black box warnings (BBW) which should appear on the leaflets of medicines for patient awareness and the prescription of drugs indicating its highly fatal adverse effects to human body. The aim of this study was to assess the knowledge of Pakistani pharmacy and medical students about BBW. A questionnaire containing contents about BBW was given to the 1st, 2nd and 3rd professional year pharmacy and medical students from different pharmacy and medical institutes. A 76% survey response rate was observed. It was observed that student’s knowledge about BBWimproves in association with the promotion in professional years of pharmacy and medical education. The results indicate that student’s knowledge about black box increases with the study level. Training in black box warnings should be implemented in pharmacy and medical institutions influencing the meaningful ways to educate and train pharmacy and medical students, and help these students to get recent knowledge about black box warnings so that, in future, they may perform an ethical practice in their respective fields.